2022
DOI: 10.3390/ijerph19095021
|View full text |Cite
|
Sign up to set email alerts
|

Postural Balance in Relation with Vision and Physical Activity in Healthy Young Adults

Abstract: Postural balance is an essential part of a wide range of activities, from daily living tasks to sports. Regularly repeated physical and/or sport activities improve both the postural performance and the postural strategy. The aim of our study was to evaluate if the physical activity level is a factor that influences postural balance performance, including the impact of vision and gender, in healthy young adults. Postural balance was assessed in 78 subjects (38 males and 40 females, aged 20.64 ± 1.18 years) by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
0
7
0
2
Order By: Relevance
“…More specifically, athletes of both team and individual sports demonstrate better body balance over the group of non-athletes ( Mocanu et al, 2022 ). Lateral CoP deviation is also lower in individuals with moderate than low physical activities ( Onofrei and Amaricai, 2022 ). However, static balance in collegiate athletes with a sport background does not differ from their multisport counterparts ( Chou et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, athletes of both team and individual sports demonstrate better body balance over the group of non-athletes ( Mocanu et al, 2022 ). Lateral CoP deviation is also lower in individuals with moderate than low physical activities ( Onofrei and Amaricai, 2022 ). However, static balance in collegiate athletes with a sport background does not differ from their multisport counterparts ( Chou et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…For healthy young people in Romania (18-25 years), there are no differences in postural balance according to gender, but the group of those who are involved in moderate physical activity has higher values of balance compared to those who have a low level of physical activism [68]. For our group, we identified the superior performance of women for most tests, even if they are only significant for the Flamingo test and Bass test (p < 0.05).…”
Section: Comparison Of Results With Similar Studies On Balance Values...mentioning
confidence: 96%
“…Specifically, there was a trend for fourth-grade students’ balance ability to change with the effect of additional visual task in physical exercise on UDVA, validating the research hypothesis. Onofrei and Amaricai ( 24 ) suggested that physical exercise and visual acuity were important factors that affected human postural balance, and that physical balance was influenced by the interaction of physical exercise and visual acuity. In this study, the partial mediating effect of UDVA on the impact of physical exercise on balance ability confirmed this view.…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al ( 23 ) have shown that vision, specific postures in sports, frequency and duration of exercise played decisive role in effects of physical activity on standing postural stability. Onofrei and Amaricai ( 24 ) pointed out that physical activity and vision were important factors affecting the postural balance of healthy students, and body balance was affected by the interaction of physical activity and vision. To sum up, children’s visual acuity had a certain impact on their balance ability.…”
Section: Introductionmentioning
confidence: 99%